СУЩНОСТЬ И ПОНЯТИЕ ПРЯМЫХ ИНОСТРАННЫХ ИНВЕСТИЦИЙ В УКРАИНЕ - Светличная, Юлия Александровна (SUPREMANCE OF LAW, 2017)
The article discusses the concepts, essence and significance of foreign direct investment as a variety of foreign investment, characterizes the dynamics of foreign direct investment in Ukraine for 2002-2016, it is emphasized that foreign direct investment is the most popular form of foreign investment, as they allow the realization of large and Long-term projects that ensure the introduction of new technologies, achievements of scientific and technological progress. The use of foreign direct investment for Ukraine is an objective necessity, due to the participation of the country’s economy in the international division of labor and the need to allocate capital in industries free from entrepreneurship. The subjects of direct foreign investment, its types and forms are shown. Attraction of foreign investments is a strategic task of the Ukrainian economy, and creation of favorable conditions for increasing the inflow of foreign investors is one of the priorities of the state economic policy of Ukraine. The advantages of direct investments and their possible negative consequences, which Ukraine should take into account, share of foreign investments are shown. Therefore, Ukraine should pursue such an economic policy of investment change in order to make maximum use of their positive influence and to eliminate or minimize possible negative consequences.